Los ingenieros docentes y el medioambiente (Revista de Diavulgación L'esprit Ingénieux, 2016)
A proposal for the formation of teachers and students in didactic processes at the Faculty of Civil Engineering University of St. Thomas, in the city of Tunja is presented. The goal is to promote the commitment to pedagogy, didactics and the responsibility with the environment. The project aims at the transformation of subjects and to produce changes in education activities to generate reflection, appropiation and new actions in accordance with the process of “learning by doing.” With the methodology of participatory research-action in education, new proposals are formulated in the formation of teachers and students. Finally, preliminary results are presented about the main didactic method used for projects
Keywords: teacher formation; learning by doing; student formation; pedagogy